Belief Uncertainty in Software Models - Burgueño-Caballero, Lola; Clarisó, Robert; Cabot, Jordi; Gérard, Sébastien; Vallecillo-Moreno, Antonio Jesús (My University, 2020)
This paper discusses the representation of Belief Uncertainty in software models. This kind of uncertainty refers to the situation in which the modeler, or any other belief agent, is uncertain about the behavior of the system, or the statements that the model expresses about it. In this work, we propose to assign a degree of belief to model statements (let they be constraints, or any other model expression), which is expressed by a probability (called credence, in statistical terms) that represents a quantification of such a subjective degree of belief. We discuss how it can be represented using current modeling notations, and how to operate with it in order to make informed decisions.
Preprint de : Loli Burgueño, Robert Clarisó, Jordi Cabot, Sébastien Gerard and Antonio Vallecillo. "Belief Uncertainty in Software Models." In Proc. of the 11th Workshop on Modelling in Software Engineering (MiSE'2019) at ICSE 2019, Montreal, Canada, May 26-27, 2019. ACM
Keywords: Incertidumbre (Teoría de la información); Modelos matemáticos; Software models; Uncertainty; Degree of belief